2017
DOI: 10.1007/s10899-017-9688-0
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Losses Disguised as Wins and Near Misses in Electronic Gaming Machines: A Systematic Review

Abstract: Near misses and losses disguised as wins have been of interest to gambling researchers and policymakers for many years (e.g., Griffiths in J Gambl Stud 9(2):101–120, 1993). This systematic literature review describes the behavioural, psychological, and psychobiological effects of near misses and losses disguised as wins (LDWs) in an effort to evaluate their precise influence on the player and to highlight areas requiring further investigation. A systematic search for relevant studies was conducted using Scopus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 71 publications
0
37
0
1
Order By: Relevance
“…Several self-report studies have demonstrated that following a session of play that includes LDWs, players tend to overestimate the frequency of winning outcomes that occurred during the session (Barton et al, 2017). Similarly, when asked to categorise events while playing, players often miscategorise LDWs as true wins (Jensen et al, 2013).…”
Section: The Science Of Ldwsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several self-report studies have demonstrated that following a session of play that includes LDWs, players tend to overestimate the frequency of winning outcomes that occurred during the session (Barton et al, 2017). Similarly, when asked to categorise events while playing, players often miscategorise LDWs as true wins (Jensen et al, 2013).…”
Section: The Science Of Ldwsmentioning
confidence: 99%
“…Research into the design of slot machines, a pervasive and widely familiar subcategory of EGMs, has identified how certain features of modern slot machines, may contribute to the high intensity of this form of gambling. These design features include: the effects of the random ratio reinforcement schedule (Turner & Horbay, ; Haw, ), the speed of play (Harris & Griffiths, ), near‐miss events (Murch & Clark, ; Barton et al ., ), free spins (Taylor et al ., ), or features such as stop buttons that foster an illusion of control (Harrigan et al ., ; Murch & Clark, ). This set of features likely work in tandem to intensify reinforcement and encourage the extended and repeat play that supports gambling revenue (Yücel et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Two other phenomena that complicate the consequential side of learning are near misses and losses disguised as wins. These are events where an omission of what is expected to be a reinforcer actually functions as a reinforcer for gambling behavior (Barton et al, 2017;Daly et al, 2014;Foxall & Sigurdsson, 2012). This is a phenomenon that is also highly relevant not only for understanding gambling behavior, but for understanding learning processes in themselves, since it appears to contradict the keystones of learning theory.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Barton et al (2017) concluded that most studies have shown that near misses motivate continued to play, but that results on the emotional state or betting behavior of the gambler show a more varied pattern. While most studies that included skin-conductance levels reported increased levels, near misses were found aversive events in a majority of studies where valence was rated.…”
Section: Reinforcement Without Winningmentioning
confidence: 99%
See 1 more Smart Citation